Keseimbangan Antara Arsitektur Tradisional dan Modern di Jalan Gajah Mada, Denpasar, Bali - Saka, Gede Ngurah Arkana Putera; Prajnawrdhi, Tri Anggraini; Wiryawan, I Wayan (Jurnal Arsitektur Universitas Udayana, 2025)
This research examines the balance between traditional and modern architecture in Jalan Gajah Mada, Denpasar, Bali, with the aim of understanding how these two architectural styles interact in a developing urban context. This study involved visual and functional analysis of the various buildings along the street, including interviews with building owners and local architectural practitioners. The research results show that the integration of traditional architecture, which is rich in ornaments and symbols of Balinese culture, with modern elements, such as minimalist design and contemporary materials, creates a unique aesthetic harmony. Modern architecture tends to adapt to current functional and aesthetic needs, while traditional elements serve as a link to cultural heritage and local identity. This research suggests the importance of a design approach that is sensitive to local context to maintain a good balance between cultural heritage preservation and urban development needs. It is hoped that these findings will provide guidance for designers and policy makers in planning and developing urban areas that reflect both. The method used in this research is a qualitative method. Key words: traditional and modern architecture in Denpasar City